2016
DOI: 10.5433/1679-0359.2016v37n1p321
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of babassu endocarp meal type II with different inclusions in sheep diets

Abstract: Industrialization of the Babassu coconut for edible oil production generates many co-products and has great potential to be used in ruminant nutrition. The aim of this study was to evaluate the effect of different inclusions of endocarp meal type II of Babassu coconut (BEMII) on intake and digestibility of sheep diets. Twenty non-castrated male sheep with an undefined breed were distributed in a completely randomized design with four treatments and five replications. The animals received an experimental diet w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
1
1
Order By: Relevance
“…In a study with sheep fed increasing levels of pineapple residue (0; 11; 16; and 27%), which is also fibrous but has higher levels of soluble carbohydrates and non-fibrous carbohydrates than BMM, Rogério et al (2007) did not find differences in gross energy digestibility and energy balance. Sá et al (2016), working with BEM reported quadratic effects with decreasing onset, contradicting the findings of the present study, which can be explained by the chemical differences between the tested materials, although they originate from the fruit of the same plant. (R 2 = 75.54%); 2 (R 2 = 82.33%); 3 (R 2 = 82.04%).…”
Section: Bmm (%)contrasting
confidence: 99%
See 1 more Smart Citation
“…In a study with sheep fed increasing levels of pineapple residue (0; 11; 16; and 27%), which is also fibrous but has higher levels of soluble carbohydrates and non-fibrous carbohydrates than BMM, Rogério et al (2007) did not find differences in gross energy digestibility and energy balance. Sá et al (2016), working with BEM reported quadratic effects with decreasing onset, contradicting the findings of the present study, which can be explained by the chemical differences between the tested materials, although they originate from the fruit of the same plant. (R 2 = 75.54%); 2 (R 2 = 82.33%); 3 (R 2 = 82.04%).…”
Section: Bmm (%)contrasting
confidence: 99%
“…Zinn (1989) showed a linear reduction of organic matter digestibility when oil was included as a supplement with inclusion levels ranging from 0 to 8%, particularly decreasing fiber digestibility. Sá et al (2016) reported that babassu endocarp meal (BEM), which has worse nutritional value than BMM, had similar impacts on digestibility to the obtained in this study. In the aforementioned work, BEM negatively influenced almost all digestibility coefficients.…”
Section: Bmm (%)supporting
confidence: 77%
“…This result demonstrates that though distinct babassu byproduct was used in this research, it has the same fibrous characteristics, which may affect the dry matter intake due to physical factors of rumen fill. Reference [22] worked with intake and digestibility of lambs fed BMF (41.0% NDF; 20.8% lignin) and also observed reductions on DM and CP digestibility. These results corroborate our data and demonstrate how lignin levels can negatively influence digestibility and promote low degradability of coproducts.…”
Section: Resultsmentioning
confidence: 99%